Assessing the Floristic Diversity and Conservation Status of Remnant Forest of Wildlife Sanctuary in Ghana using Geostatistics and Genetic Heat Index (Global Journal of Science Frontier Research, 2018)
The study assessed the conservation status and the diversity of the floristic components of the UENR’s wildlife sanctuary using the Geostatistical tools and Genetic Heat Index (GHI). Twenty-nine (29) sampling plots were randomly located using the “create random points” algorithm in ArcGIS 10.4. A three-nest sampling plots of 10m x 10m, 5m x 5m and 1m x 1m were laid for the enumeration of Trees (DBH > 10 cm), Saplings (>2 cm DBH < 10 cm) and Seedlings (≤1m height or < 2 cm girth), respectively. The Shannon Wiener’s Diversity Index (H’), Species Richness (S) and GHI were used to assess the diversity, abundance, and conservation status of the Trees, Saplings and Seedlings species enumerated. Overall, 460 floral individuals belonging to 58 species and 28 families were recorded. The Trees species were more diverse (1.05 ± 0.10) compared to the sapling and seedling growth forms, which had diversity indices of 0.95 (±0.10) and 1.03 (± 0.08), respectively. Further, the Green star species were the dominant species in all the different diameter classes, representing 58%, 67% and 77% of the total number of species of Trees, Saplings, and Seedlings, respectively. Only a single black star seedling (Psychotria ankasensis) species was recorded. The dominants families were Fabaceae (15.6%), Sapindaceae (11.2%), Moraceae (8.9%), Apocynaceae (8.9%) and Rubiaceae (5.6%). The tree species had the lowest conversation status (GHI = 8.13), followed by saplings which obtained a low conservation status (GHI = 62.50), while seedlings had “very high” conversation status (GHI = 269.38). The study recommended that strict protection and management of entire floristic components should be undertaken to promote sustainable conservation of the remnant forest in the wildlife sanctuary.
Keywords: species diversity; genetic heat index; conservation status; geostatistics; wildlife sanctuary; Ghana